Genome-wide identification and expression analysis of CBF/DREB1 gene family in Medicago sativa L. and functional verification of MsCBF9 affecting flowering time - Jing Cui; Yajing Li; Hao Liu; Xu Jiang; Lili Zhang; Hongbo Dai; Xue Wang; Fei He; Mingna Li; Junmei Kang (BMC Plant Biology)
Abstract Background The C-repeat binding factor (CBF)/dehydration-responsive element binding (DREB1) belongs to a subfamily of the AP2/ERF (APETALA2/ethylene-responsive factor) superfamily, which can regulate many physiological and biochemical processes in plants, such as plant growth and development, hormone signal transduction and response to abiotic stress. Although the CBF/DREB1 family has been identified in many plants, studies of the CBF/DREB1 family in alfalfa are insufficient. Results In this study, 25 MsCBF genes were identified in the genome of alfalfa (“Zhongmu No. 4”). These genes were distributed on chromosomes 1, 5, 6 and unassembled scaffolds. Phylogenetics divided the CBF members of Medicago sativa, Arabidopsis thaliana, and Medicago truncatula into six groups, of which group VI had the most MsCBFs members, reaching 52% (13/25). Gene duplication analysis showed that 64% (16/25) of MsCBFs formed tandem duplications, and 32% (8/25) formed segment duplications. The expression pattern of MsCBF9 under different hormone treatments was verified by RT-qPCR, and it was found that MsCBF9 responded to GA3, IAA, SA, and MeJA. Overexpression of MsCBF9 in Arabidopsis significantly delayed the flowering time of Arabidopsis. In contrast, the flowering time of the cbfs mutant was earlier, and overexpression of MsCBF9 also increased the number and size of Arabidopsis rosette leaves. Conclusion In this study, the CBF/DREB1 family of alfalfa was comprehensively identified and analyzed, and the function of MsCBF9 in regulating flowering time was studied. This study laid a foundation for further analysis of the function of the CBF family in alfalfa. Clinical trial number Not applicable.